SEPUTAR REAKSI HIPERSENSITIVITAS (ALERGI) - Hikmah, Nuzulul; Dewanti, I Dewa Ayu Ratna (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
Introduction. Till now allergy was a piquancy to be submitted, because most all people have everexperienced it. Symptom and also allergen all kinds and varies can come from neither outside body nor in bodyxself. Purpose of Writing. Co-signature deeper in around allergic reaction. Discussion. Allergic reaction is immunesystem trouble marked by abundant reaction from immune response. Allergic reaction entangles allergen, is causingcells discharges matters or mediator chemistry which can destroy or hurts network in vinicity. Allergen can in the formof mote, crop powder, drug or food, is acting as antigen stimulating the happening of immune responds. Allergicreaction divided to become allergic reaction type I entangling Ig E, type II Antibody-Mediated Cytotoxi ity ( Ig G),type III ( Immune Complex Disorders) and type IV (delayed hypersensitivities). Conclusion. Allergic reaction is caused[by] allergen having manifestation to vary and divided to become reaction quickly ( type I), type II, type III and typeIV.